Examining the influence of burnout on job performance among selected civil servants in Abeokuta, Ogun State, Nigeria - Abiodun Adekunle Ogunola; Stella Ogooluwa Daniel (Journal of Science and Inclusive Development, 2026)
The feeling of being drained, detached, and ineffective from work is a problem that contradicts the well-being of civil servants. However, there is limited research on exploring the influence of burnout on job performance among civil servants. The study examined the influence of burnout on job performance among civil servants in Abeokuta, Ogun State, Nigeria. The study consisted of 240 participants as employees within the civil service, who represent various departments. Three hypotheses were formulated and tested with the use of linear regression analysis. The research instruments used are the Maslach Burnout Inventory (MBI-HSS) and the Individual Work Performance Questionnaire (IWPQ). The findings of the research indicated that burnout significantly influenced the contextual performance of the employees. The results also indicated that burnout significantly influenced the counterproductive work behavior of the workers, indicating that when the burnout is not mitigated, it could lead to increased absenteeism and presenteeism, thereby affecting diminished work output and overall productivity. Establishing support systems, such as stress management training and fostering a supportive workplace culture, can help alleviate burnout. Empowering civil servants by giving them more control over their tasks and decisions can boost job satisfaction and motivation and therefore improve the performance of their jobs significantly.